Cardiovascular pathophysiology, epidemiology, and treatment 2 considerations of coronavirus disease 2019 (covid-19): A review (2020)
The coronavirus disease 2019 (COVID-19) pandemic caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is rapidly evolving, with important cardiovascular considerations. The presence of underlying cardiovascular risk factors and established cardiovascular disease (CVD) may affect the severity and clinical management of patients with COVID-19. We conducted a review of the literature to summarize the cardiovascular pathophysiology, risk factors, clinical presentations, and treatment considerations of COVID-19 patients with underlying CVD. The angiotensin-converting enzyme 2 (ACE2) enzyme has been identified as a functional receptor for the SARS-CoV-2 virus, and is associated with the cardiovascular system. Hypertension, diabetes, and CVD are the most common comorbidities in COVID-19 patients, and these factors have been associated with the progression and severity of COVID-19. However, elderly populations, who develop more severe COVID-19 complications, are naturally exposed to these comorbidities, underscoring the possible confounding of age. Observational data supports international cardiovascular societies’ recommendation to not discontinue ACEi/ARB therapy in patients with guideline indications out of fear for the increased risk of SARS-CoV-2 infection, severe disease, or death. In addition to the cardiotoxicity of experimental antivirals and potential interactions of experimental therapies with cardiovascular drugs, several strategies for cardiovascular protection have been recommended in COVID-19 patients with underlying CVD. Troponin elevation is associated with increased risk of in-hospital mortality and adverse outcomes in patients with COVID-19. Cardiovascular care teams should have a high index of suspicion for fulminant myocarditis-like presentations being SARS-CoV-2 positive, and remain vigilant for cardiovascular complications in COVID-19 patients.